Parental Leave Benefit and Differential Fertility Responses: Evidence from a German Reform - Kamila Cygan-Rehm (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper examines the causal effects of a major change in the German parental leave benefits on fertility. I use the unanticipated reform of 2007 to assess how a move from a means-tested to an earnings-related benefit affects higher-order births. By using data from the Mikrozensus, I find that the reform significantly affected the timing of higher-order births. Overall, mothers “just” affected by the reform initially reduce subsequent childbearing and start to compensate by the end of the third year. The negative effects are largely driven by lowest-income mothers, who are now worse-off and do not display any catch-up effects.
Keywords: J13; J18; J20; K36; 330; fertility; family policy; reform; parental leave; Germany